Unilateral Maxillary Canine Agenesis: A Case Report and Literature Review - Nagihan Koç; L. Berna Çağırankaya; Nursel Akkaya (Case Reports in Dentistry)
Congenital absence of maxillary permanent canines is an extremely rare condition, which may appear as part of a syndrome or as a nonsyndromic form. Nonsyndromic canine agenesis combined with other types of tooth agenesis has occasionally been described in the literature but isolated cases are rarely observed. This report presents an isolated case of maxillary permanent canine agenesis in a healthy 18-year-old female patient and a literature review on the prevalence, etiology, and differential diagnosis of the condition.